High SARS-CoV-2 seroprevalence in Lagos, Nigeria with robust antibody and cellular immune responses - Sulaimon Akanmu; Bobby Brooke Herrera; Beth Chaplin; Sade Ogunsola; Akin Osibogun; Fatima Onawoga; Sarah John-Olabode; Iorhen E. Akase; Augustina Nwosu; Donald J. Hamel; Charlotte A. Chang; Phyllis J. Kanki (Journal of Clinical Virology Plus, 2023)
Background: Early evidence suggested that the impact of the COVID-19 pandemic was less severe in Africa compared to other parts of the world. However, more recent studies indicate higher SARS-CoV-2 infection and COVID-19 mortality rates on the continent than previously documented. Research is needed to better understand SARS-CoV-2 infection and immunity in Africa. Methods: In early 2021, we studied the immune responses in healthcare workers (HCWs) at Lagos University Teaching Hospital (n = 134) and Oxford-AstraZeneca COVID-19 vaccine recipients from the general population (n = 116) across five local government areas (LGAs) in Lagos State, Nigeria. Western blots were used to simultaneously detect SARS-CoV-2 spike and nucleocapsid (N) antibodies (n = 250), and stimulation of peripheral blood mononuclear cells with N followed by an IFN-γ ELISA was used to examine T cell responses (n = 114). Results: Antibody data demonstrated high SARS-CoV-2 seroprevalence of 72·4% (97/134) in HCWs and 60·3% (70/116) in the general population. Antibodies directed to only SARS-CoV-2 N, suggesting pre-existing coronavirus immunity, were seen in 9·7% (13/134) of HCWs and 15·5% (18/116) of the general population. T cell responses against SARS-CoV-2 N (n = 114) were robust in detecting exposure to the virus, demonstrating 87·5% sensitivity and 92·9% specificity in a subset of control samples tested. T cell responses against SARS-CoV-2 N were also observed in 83.3% of individuals with N-only antibodies, further suggesting that prior non-SARS-CoV-2 coronavirus infection may provide cellular immunity to SARS-CoV-2. Conclusions: These results have important implications for understanding the paradoxically high SARS-CoV-2 infection with low mortality rate in Africa and supports the need to better understand the implications of SARS-CoV-2 cellular immunity.